Kecenderungan keusahawanan sosial dalam kalangan pelajar Universiti Utara Malaysia - Nor Syakira, Kasim (2015)
This study aimed to exploresocial entrepreneurial intention among Universiti Utara Malaysia (UUM) students. There are five objectives of this study, namely: (1) to determinethe level of social entrepreneurial intention among UUM student; (2) to examine the level of attitude, social norm, perceived behavioural control on social entrepreneurship among UWM students; (3) to identify social entrepreneurship differences based on demographic factors; (4) to identify relationship between attitude, social norm and perceived behavioral control on social entrepreneurship towards social entrepreneurial intention; (5) to identified influence of attitude, social norm and perceived behavioral control on social entrepreneurship towards social entrepreneurial intention. The Theory of Planned Behavior (Ajzen, 1991) was used as the basis for the study. This study used quantitative approach with survey method and questionnaire was used for data collection. The sample consisted of 385 undergraduate students at UUM. The findings showed that the levels of social entrepreneurial intention, social norm, and perceive behavior control among ULTM students were moderately high, except for attitude which was at the high level. This study also showed differences in social entrepreneurial intention based on participation in entrepreneurship courses in UUM, family background in voluntary activity and students experience as a voluntary. However, there was no significant difference in social entrepreneurial intention based on close family background in business. Pearson correlation analysis showed a significant relationship between attitudes, perceived behavioral control on social entrepreneurship, and social norms toward social entrepreneurial intention. Multiple regression analysis also showed that the attitude has the highest influence on the social entrepreneurial intention, followed by the social norm and perceived behavioral control on social entrepreneurship. The implications of this research is that, in order to inculcate and increase social entrepreneurial intention among university students, the university should take into consideration the factor of attitude, social norm and perceived control behavior on social entrepreneurship while enhancing social entrepreneurial activities that can be attended by students.